Biofortification of brinjal with zinc and iron through fortified organics optimized NPK and bioactive compounds and their effects on the growth yield and quality of brinjal and on soil properties in coastal saline soil - Kamaleshwaran, R; Elayaraja, D (Plant Science Today, 2026)
Eggplant (aubergine or brinjal) is an important vegetable crop grown worldwide which is valued for its richness in dietary fibre and essential minerals such as calcium, iron, phosphorus and potassium. Brinjal is considered a heavy feeder of nutrients due to its long duration and high yield potential. In coastal nutrient-deficient soils, it is often cultivated without adequate nutrient management practices. To address this challenge, field experiments were conducted in a Randomized Block Design (RBD) with three replications. The trials were carried out during the kharif (2022–2023) and rabi (2022–2023) seasons in Ayikuppam village, Cuddalore district, Tamil Nadu. The study aimed to evaluate the effects of zinc and iron biofortification through fortified organics, optimised NPK and bioactive compounds on the growth, yield and quality of brinjal, as well as on soil properties in coastal saline soil. In both seasons, biofortification of brinjal with optimised dose of 150 % NPK + Zn and Fe fortified CCP at 6.25 t ha-1 + 50 % ZnSO4 and FeSO4 at 12.5 kg ha-1 along with foliar spray of ZnSO4 & FeSO4 at 0.5 % + Napthalene acetic acid (NAA) at 50 ppm + humic acid (HA) and sea weed extract (SWE) at 0.2 % at vegetative stage (VS) and flowering stages (FS) resulted in significantly higher mean plant height (121.97 cm), number of branches (40.24) number of fruits plant-1 (35.97), single fruit weight (56.49 g), fruit length (31.77 cm), fruit (32.95 t ha-1) and stover yield (47.88 t ha-1) compared to control. This treatment also improved the quality of brinjal and soil properties of coastal land.